2006
DOI: 10.1002/gcc.20315
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of early adenocarcinoma of the esophagus or gastroesophageal junction: Tumor progression is associated with alteration of 1q and 8p sequences

Abstract: Early (T1 stage) adenocarcinoma of the esophagus or gastroesophageal junction is a potentially curable disease. We analyzed the genomic spectra of 33 early neoplastic lesions after subdividing the tumors into six depths of invasion (T1-mucosal, m1-m3; T1-submucosal, sm1-sm3). Two subgroups were defined, T1m1-sm1 (n = 18) and T1sm2-sm3 (n = 15). The latter group is associated with frequent lymphatic spread and a high percentage of local and/or distant recurrence. Comparative genomic hybridization with a genomew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Studies carried out by classical CGH have demonstrated multiple chromosomal copy number changes, including gains in chromosomes 6q, 7p, 7q, 8q, 11q, 15q, 17q, and 20q, as well as losses at chromosomes 1p, 3p, 4p, 4q, 5q, 8p, 9p, 17p, and 18q. [4][5][6][7][8]14 However, the minimal amplified region detected by conventional CGH usually spans several megabases, making it difficult to identify specific candidate genes involved in tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies carried out by classical CGH have demonstrated multiple chromosomal copy number changes, including gains in chromosomes 6q, 7p, 7q, 8q, 11q, 15q, 17q, and 20q, as well as losses at chromosomes 1p, 3p, 4p, 4q, 5q, 8p, 9p, 17p, and 18q. [4][5][6][7][8]14 However, the minimal amplified region detected by conventional CGH usually spans several megabases, making it difficult to identify specific candidate genes involved in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent DNA gains on chromosome 6p have been reported in esophageal adenocarcinoma, 6,7,15 but to date they have not been well characterized. Our analysis revealed that besides VEGF amplification (6p12) common to 50% of esophageal adenocarcinoma samples, other alterations were found exclusively or mostly in the r20-month survival subgroup, such as gain of KIAA0170 and IER3 genes at 6p21.3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spot intensities were measured with GenePix Pro 5.1 software (Axon Instruments). Further analyses were done using Microsoft Excel 2000 (15,16).…”
Section: Cancer Researchmentioning
confidence: 99%